The Influence of Marketing Mix and Word of Mouth Towards Brand Image and Usage of Online Bike Usage - Fandi Yanuar Rahman; Lilik Noor Yuliati; Megawati Simanjuntak (School of Business, IPB University (SB-IPB), 2019)
This research aimed to analyze the influence of marketing mix and word of mouth towards brand image and the usage of online bike. The research design used descriptive, with the survey conducted using questionnaire as the tool of interview. The sampling technique used systematic random sampling with a kish grid approach. Kish grid is a method for selecting members within a household to be interviewed, this method was commonly used in marketing research especially on household survey. The exact 200 samples were obtained for the research. There were four latent variabels in this research, included marketing mix and word of mouth as independent variables, brand image as intervening variables and the usage of online bike as dependent variables. The datawere processed using descriptive through SPSS 24 and Structural Equation Modelling (SEM) method by LISREL 8.7 software. The results of this research revealed thatmarketing mix influenced positively and significantly toward the brand image; word of mouth influenced positively and significantly toward the brand image; marketing mix influenced positively and significantly toward the usage of online bike; word of mouth influenced positively and significantly toward the usage of online bike; and brand image influenced insignificantly toward the usage of online bike.Keywords: marketing mix, brand image, word of mouth, online bike, service usage